Fluoride releasing restorative materials: a review - Neti, Brunda; Sayana, Gowthami; Muddala, Lahari; Mantena, Satyanaryana Raju; Yarram, Anusha; GVD, Harsha (International Journal of Dental Materials, 2020)
Fluoride compounds are incorporated as anticariogenic agents in numerous restorative materials. Incorporation of fluoride into restorative materials impart anticariogenic character by various mechanisms including reduction of demineralisation, enhancement of remineralisation, interference of pellicle and plaque and inhibition of microbial growth and metabolism. In addition, the application of the topical fluoride in the form of toothpaste and varnish is also considered as the most effective method of caries prevention. The fluoride combines with HA of the tooth and forms an acid-resistant fluorapatite (FAP) crystals. Also, fluoride enters into the cells of the bacteria and inhibits carbohydrate metabolism, which eventually kills the bacteria. The objective of this review was to emphasise the fluoride-releasing restorative materials available in dentistry.